Pertumbuhan EKonomi Pengaruh Machine Knowledge, Training of Trainer dan Repair Technician Grade Terhadap Produktivitas Kerja Teknisi - Rahmat Iqbal Yuanda; Fauzan; Janusi Waliamin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Employee productivity is a very important thing in the company's efforts to achieve its goals. The purpose of this study was to determine how influential the Machine Knowledge, Training of Trainer and Grade variables had on work productivity. The population of this study were Honda Arista employees in Bengkulu City, totaling 70 employees with a sample of 31 employees. The sampling technique is purposive sampling. This research is explanatory research using a quantitative approach which explains the effect of the Knowledge (X1), Training of Trainer (X2) and Repair Technician Grade (X3) variables on technician work productivity (Y). The results showed that the Knowladge variable had a significant effect on the technician's work productivity, the Training of trainer variable also had a significant effect on the technician's work productivity, then the grade variable had a significant effect on the technician's work productivity. Overall, the results of the study show that the Knowledge (X1), Training of Trainer (X2) and Repair Technician Grade (X3) variables have a significant effect on work productivity (Y).